Answer :

=Sin3x+sin2x-sinx


= (sin3x- sinx)+sin2x


= ( 2cossin) + sin2x


= 2cos2xsinx +sin2x


= 2cos2xsinx + 2sinxcosx


= 2sinx (cos2x + cosx )


= 2sinx (2cos cos )


= 4sinxcos cos


Using the formula,


sinA - sinB = 2cos sin


cosA + cosB = 2coscos


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

In a ΔABC, if <spRD Sharma - Mathematics

For any Δ ABC shoRD Sharma - Mathematics

Two ships leave aRD Sharma - Mathematics

In a Δ ABC cos<suRD Sharma - Mathematics

In any Δ ABC, <spRD Sharma - Mathematics

In a Δ ABC cos<suRD Sharma - Mathematics

Two ships leave aRD Sharma - Mathematics

In any Δ ABC, <spRD Sharma - Mathematics

For any Δ ABC shoRD Sharma - Mathematics

For any Δ ABC shoRD Sharma - Mathematics